Saleeva Antonina Denisovna - Рrotezirovania UkrNII (ORTHOPAEDICS TRAUMATOLOGY and PROSTHETICS, 2017)
The article is devoted to the jubilee of the director of the Ukrainian Research Institute of Prosthetics, Prosthesis Building and Restoration of Work Ability, Candidate of Technical Sciences, Associate Professor A. Saleeva.